A Normalized Dragon: Constructing China's Security Identity. (4th August 2013) - Ogden, Chris
Abstract : What has structured Chinese security practice over the last 100 years since the Xinhai (1911) Revolution? Moreover, what are the ideational principles and norms that have influenced China's international relations? Employing an analytical framework concerning norm creation ("security identity"), this article details how different norms originated, became established and subsequently served to orientate Chinese foreign policy behavior. Such a process has been critically informed by China's international interaction, learning and experience across the last 100 years, revealing how past relations can inform present and future conduct. Undertaking an analysis in this fashion implies not so much how a state "should" behave but instead indicates the broad continuities structuring its security practice. From the focus upon security identity (which gives ideational rather than structural explanations of security behavior), our analysis rests upon the elucidation of three inter‐related normative sources. These three sources have been tempered via the interplay between China's international interaction and internal political developments, and show the ideational precedents in China's foreign policy behavior. The three sources are: (i) the political (internal political developments); (ii) the physical (relations with neighboring/bordering states); and (iii) the perceptual (conceptions of self, the international system and their mutual relationship). Overall, the article finds a relative consistency to how security has been ideationally conceived of in China, and highlights three core norms essential to such a conception – centralized control, territorial restoration, and (re)becoming a great power.